(untitled) (GESTIÓN Y TENDENCIAS, 2024)
This article synthesizes the main economic theories of the demand for money based on the work of David Laidler. The study traces the evolution of monetary thought from Fisher’s classical approach and the Quantity Theory, through the Cambridge perspective that introduces opportunity cost and wealth, to the Keynesian revolution with its transaction, precautionary, and speculative motives. It then examines Friedman’s modern quantity theory, which treats money as an asset that provides services and whose demand depends on the return on alternative assets and on human wealth. The text offers a structured guide to understanding how the relationship between money, prices, and human behavior determines the effectiveness of fiscal and monetary policy.